Identificationof a novel linear epitope on the porcine reproductive and respiratory syndrome virus nucleocapsid protein, as recognized by a specific monoclonal antibody - Cheng, Yuening; Wu, Miaoli; Xiao, Li; Zhang, Mengdi; Huang, Bihong; Cong, Feng; Yi, Li (Frontiers in Immunology, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) remains one of the most threatening pathogens of swine. The nucleocapsid (N) protein is the major structural protein of the virus and has been used as a PRRSV diagnostic antigen due to its high level of inherent immunogenicity. In this study, a specific monoclonal antibody mAb (N06) that could recognize both the denatured form as well as the native form of N protein was produced. A linear epitope of N protein was subsequently identified by enzyme-linked immunosorbent assays (ELISA) using the synthesized overlapping peptides as antigens. The results revealed that mAb N06 recognized the epitope NRKKNPEKPHFPLATE, which was consistent with BCPREDS predictions of antigenicity. All the data suggested that the mAb (N06) can be used as diagnostic reagents while the recognized linear epitope can be useful in epitope-based vaccines development, which is helpful for the control of local PRRSV infections in swine.